Real Earnings Management and Long-Term Operating Performance: The Role of Reversals in Discretionary Investment Cuts - Vorst, Patrick (The Accounting Review, 2016)
ABSTRACT I examine whether a reversal of an abnormal cut in discretionary investments is associated with the degree to which the cut is reflective of real earnings management (REM) and whether and how it predicts future operating performance. I define a reversal as occurring when a firm cuts discretionary investments to a below-expected level in one period and reverts back to at least the expected level of investment during the next period. Unlike accrual earnings management, REM involves deliberately altering the operations of the firm to influence reported accounting numbers. To the extent that such interventions diverge from optimality, they can expose the firm to real economic costs. I find that a reversal of an abnormal cut in discretionary investments in the year after the cut has taken place is indicative of REM. I further find that, on average, reversing cuts are associated with lower future operating performance, but that such results vary significantly depending on the various incentives to engage in REM, as well as other factors that affect its associated costs and benefits. These findings are of interest to investors, regulators, and academics with respect to the identification and consequences of REM.